2015
DOI: 10.1088/1612-2011/12/4/045202
|View full text |Cite
|
Sign up to set email alerts
|

Slow light propagation and bistable switching in a graphene under an external magnetic field

Abstract: In this letter, we show the possibility of controlling the optical bistability and group index switching in graphene under the action of strong magnetic and infrared laser fields. By using quantum-mechanical density matrix formalism, we obtain the equations of motion that govern the optical response of graphene in strong magnetic and optical fields. We found that by properly choosing the parameters of the system, the bistable behaviors and group velocity can be controlled. These results may have potential appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 54 publications
0
46
1
Order By: Relevance
“…52,53 Based on these prominent studies, we have studied numerically the slow light propagation and bistable switching in graphene under an external magnetic field with four level energy levels and in lambda configuration. 54 In the current paper, we intend to investigate both numerically and analytically the behavior of OB and optical multistability (OM) in the quantized fourlevel graphene medium in a cascade-type scheme. We show that under the action of an external magnetic field the shape of the OB curve and subsequently the OB threshold can be significantly modified by changing the intensity of the control fields, which is due to the unique flexability and strong nonlinearity of graphene.…”
Section: Realization Of Optical Bistability and Multistability In Lanmentioning
confidence: 99%
“…52,53 Based on these prominent studies, we have studied numerically the slow light propagation and bistable switching in graphene under an external magnetic field with four level energy levels and in lambda configuration. 54 In the current paper, we intend to investigate both numerically and analytically the behavior of OB and optical multistability (OM) in the quantized fourlevel graphene medium in a cascade-type scheme. We show that under the action of an external magnetic field the shape of the OB curve and subsequently the OB threshold can be significantly modified by changing the intensity of the control fields, which is due to the unique flexability and strong nonlinearity of graphene.…”
Section: Realization Of Optical Bistability and Multistability In Lanmentioning
confidence: 99%
“…The optomechanical system plays a significant role in the manipulation of mechanical resonators and electromagnetic fields, and leads to extensive topics, such as gravitational-wave detectors 1 2 3 , cooling of mechanical resonators 4 5 6 7 8 9 10 , single-photon transport 11 , optomechanically induced transparency(OMIT) 12 13 14 15 16 17 , and some other meaningful investigations 18 19 20 21 22 23 24 43 44 45 . OMIT is an analog of electromagnetically induced transparency(EIT) 25 26 27 28 , which provides an effective approach of controlling electromagnetic fields and the optical characteristics of matter.…”
mentioning
confidence: 99%
“…In Refs. [54][55][56][57][58][59][60][61][62][63] it has been demonstrated that the optical transitions between adjacent Landau levels in graphene for magnetic field 0.01-10 T fall into terahertz and infrared region according to…”
Section: Model and Equationsmentioning
confidence: 99%
“…Moreover, due to growing high quality epitaxial graphene and combination of uncommon electronic features with extraordinary optical properties, they are very favoraitable for applications in infrared and terahertz optics [51][52][53]. Some optical properties of graphene [54][55][56][57][58][59][60][61][62][63] based on the nonlinear optical interaction in the presence of strong magnetic field have been analyzed. For example, generation of polarization entangled photons [54], generation and propagation of ultraslow optical solitons [57,58], controlling the optical bistability and multistability [61][62][63] have been reported very recently.…”
Section: Introductionmentioning
confidence: 99%